Menyoal Penafsiran Al-Khazin Dalam Tafsir Lubab Al-Ta’wil Fi Ma’ani Al-Tanzil - Zulfikri Zulkarnaini (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Tafsir al-Khazin emerged in the early of the affirmative era. This paper attempts to reveal; 1), The socio-historical background of this interpretation appears. 2) trying to describe-analyze a set of understandings of essential definitions such as al-Qur'an, interpretation, ta'wil, the use of hadith, fiqh, and Israiliyat, 3). Explaining the